Prevalence and phylogenetic analysis of porcine circovirus type 2 (PCV2) and type 3 (PCV3) in the Southwest of China during 2020–2022 - Yang, Yanting; Xu, Tong; Wen, Jianhua; Yang, Luyu; Lai, Siyuan; Sun, Xiangang; Xu, Zhiwen; Zhu, Ling (Frontiers in Veterinary Science, 2022)
Introduction Porcine circovirus type 2 (PCV2) is considered one of the viruses with substantial economic impact on swine industry in the word. Recently, porcine circovirus type 3 (PCV3) has been found to be associated with porcine dermatitis and nephropathy syndrome (PDNS)-like disease. And the two viruses were prone to co-infect clinically. Methods To further investigate the prevalence and genetic diversity of the two viruses, 257 pig samples from 23 different pig farms in southwest China with suspected PCVAD at different growth stages were analyzed by real-time PCR between 2020 and 2022 to determine the presence of PCV2 and PCV3. Results Results showed high prevalence of PCV2 and PCV3: 26.46% samples were PCV2 positive and 33.46% samples were PCV3 positive. The coinfection rate was doubled from 2020 (5.75%) to 2022 (10.45%). Subsequently, the whole genome sequences of 13 PCV2 and 18 PCV3 strains were obtained in this study. Of these, 1 strain was PCV2a, 5 strains were PCV2b and 7 strains were PCV2d, indicating that PCV2d was the predominant PCV2 genotype prevalent in the Southwest of China. Discussion In addition, the phylogenetic analysis of PCV3 showed high nucleotide homology (>98%) between the sequences obtained in this study and reference sequences. And 3 mutations (A24V, R27K and E128D) were found in PCV3 antibody recognition domains, which might be related to the mechanism of viral immune escape. Thus, this study will enhance our understanding of the molecular epidemiology and evolution of PCV2 and PCV3, which are conducive to the further study of the genotyping, immunogenicity and immune evasion of PCVs.